ANALISIS PENGARUH TALENT MANAGEMENT TERHADAP ORGANIZATIONAL PERFORMANCE DAN DAMPAKNYA PADA EMPLOYEE RETENTION - Isanawikrama, Isanawikrama; Wibowo, Faisal Armand; Buana, Yud; Kurniawan, Yohannes Jhony (Jurnal Administrasi dan Kesekretarisan, 2017)
The purpose of this study is to determine whether talent management has a significant effect on Organizational Performancedan impact on Employee retention. The research method used is survey method with type of associative research, and case study. The author took samples of 31 employees of PT X headquarters. Data were collected by questionnaire in the form of questionnaires. Data analysis method used is Partial Least Square (PLS) with the help of smartPLS 2.0 software. The results of this study indicate that Talent management has a positive and significant effect on Organizational Performancedan impact on Employee retention. Better Talent Management Organizational performancedan impact on Employee retention will increase. Suggestion given in this research is to improve leadership improvement program and give encouragement to increase organizational performance which of course will affect employee retention. By improving talent management practice, it is expected to improve organizational performance and achieve company goals.